Long‐term Mortality in Pediatric Firearm Assault Survivors: A Multicenter, Retrospective, Comparative Cohort Study. (13th November 2018) - Shaahinfar, Ashkon; Yen, Irene H.; Alter, Harrison J.; Gildengorin, Ginny; Pan, Sun‐Ming J.; Betts, James M.; Fahimi, Jahan
Abstract: Objectives: The objective was to determine whether children surviving to hospital discharge after firearm assault (FA) and nonfirearm assault (NFA) are at increased risk of mortality relative to survivors of unintentional trauma (UT). Secondarily, the objective was to elucidate the factors associated with long‐term mortality after pediatric trauma. Methods: This was a multicenter, retrospective cohort study of pediatric patients aged 0 to 16 years who presented to the three trauma centers in San Francisco and Alameda counties, California, between January 2000 and December 2009 after 1) FA, 2) NFA, and 3) UT. The Social Security Death Master File and the California Department of Public Health Vital Statistics (2000–2014) were queried through December 31, 2014, to identify those who died after surviving their initial hospitalization and to delineate cause of death. Multivariate Cox proportional hazards regression was performed to determine associations between exposure to assault and long‐term mortality. Results: We analyzed 413 FA, 405 NFA, and 7, 062 UT patients who survived their index hospital visit. A total of 75 deaths occurred, including 3.9, 3.2, and 0.7% of each cohort, respectively. Two‐thirds of all long‐term deaths were due to homicide. After multivariate adjustment, adolescent age, male sex, black race/ethnicity, and public insurance were independent risk factors for long‐term mortality. FA (adjusted hazard ratio [AHR] = 1.8, 95% confidence interval [CI] = 0.82–4.0) and NFA (AHR = 1.9, 95% CI = 0.93–3.9) did not convey a statistically significant difference in risk of long‐term mortality compared to UT. Being assaulted by any means (with or without a firearm), however, was an independent risk factor for long‐term mortality in the full study population (AHR = 1.9, 95% CI = 1.01–3.4) and among adolescents (AHR = 1.9, 95% CI = 1.01–3.6). Conclusion: Children and adolescents who survive assault, including by firearm, have increased long‐term mortality compared to those who survive unintentional, nonviolent trauma.